(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The pedagogical foundations of raising children in Uzbek families are rooted in national values such as respect for elders, hospitality, religious teachings, and labor education. These values shape children’s character, ensuring moral integrity and cultural identity. Through storytelling, experiential learning, and family traditions, Uzbek families integrate traditional pedagogy with modern educational methods to prepare children for the complexities of globalization while preserving their heritage.